Activation of B1 B cells by F. tularensis atypical LPS depends on classical complement and C3a - Melo, Guilherme; Barbosa, Carlos Henrique D.; Magrini, Elena; Garlanda, Cecilia; Re, Fabio (PLOS Pathogens, 2025)
Author summary The lipopolysaccharide (LPS) of the bacterium Francisella tularensis strongly stimulates B cells for antibody production independently of T cell help through unknown mechanism. In the present study we examined the role of the complement cascade in this process. We found that production of antibodies against this LPS depends on activation of the classical complement pathway but not the MBL-dependent lectin or the alternative pathways. Following complement activation, LPS became tagged with the C3d complement fragment leading to its interaction with the complement receptor CR2 expressed by B cells. Complement activation also resulted in production of the anaphylatoxin C3a that was required for B cells activation, possibly through induction of IL-5 by innate lymphoid cells 2. Our study increases our understanding of the B cells’ response to T-independent antigens and identifies two complement effector mechanisms that can be harnessed for therapeutic interventions.